2022
DOI: 10.1016/j.archger.2021.104606
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdowns’ effects on the quality of life, perceived health and well-being of healthy elderly individuals: A longitudinal comparison of pre-lockdown and lockdown states of well-being

Abstract: Purpose. The concept of lockdown in relation to COVID-19 is thought to have an indirect impact on the quality of life and well-being of the elderly due to its consequences on the physical, psychological, and cognitive health of individuals. However, previous published studies on this subject are limited in terms of methodological approach used, including the absence of pre-confinement status and the type of experimental design, which is often cross-sectional. The present study proposes a longitudinal design wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 51 publications
4
41
0
10
Order By: Relevance
“…A decrease in the perceived quality of life, mental health and well-being was observed in previous studies during the lockdown in healthy elderly persons 12 , Brazilian population 25 , and Italian adults 14 , 26 . Actually, Bordeur and colleagues 13 reported a substantial increase in the online search intensity for topics related to boredom, loneliness, worry, and sadness, and a substantial reduction of users’ interest about stress, suicide, and divorce topics in Europe and the US.…”
Section: Technical Validationsupporting
confidence: 50%
See 1 more Smart Citation
“…A decrease in the perceived quality of life, mental health and well-being was observed in previous studies during the lockdown in healthy elderly persons 12 , Brazilian population 25 , and Italian adults 14 , 26 . Actually, Bordeur and colleagues 13 reported a substantial increase in the online search intensity for topics related to boredom, loneliness, worry, and sadness, and a substantial reduction of users’ interest about stress, suicide, and divorce topics in Europe and the US.…”
Section: Technical Validationsupporting
confidence: 50%
“…Besides the serious economic damages, social and psychological negative effects of social distancing and isolation have been quickly recognised by the scientific community 4 , 5 and government itself. Since the COVID-19 diffusion, several studies demonstrated that the lockdown periods negatively affected mental health 6 , sleep- 7 – 10 and physical activity-related behaviors 11 , overall contributing to reduced well-being and quality of life 12 14 . This picture illustrates the immediate dramatic consequence of home-confinement, that Italian and other governments worldwide adopted to limit the COVID-19 diffusion and preserve citizens’ health.…”
Section: Background and Summarymentioning
confidence: 99%
“…In addition, both perceived energy and fatigue are recognized as prominent symptoms of various mental health conditions, including depression, anxiety, and insomnia [84]. More pertinently to the COVID-19 outbreak and associated lockdowns, it has been recently reported that pre-lockdown energy levels represented a negative predictor for quality of life in a cohort of physically active elderly people and that lower energy levels during lockdowns correlated with lower well-being perceptions [85].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Canada found that quality of life and wellbeing worsened over time in the period between before lockdown and 3 months after the first lockdown began and between the period before lockdown and the second lockdown. In contrast, they did not find any difference between the two lockdown periods (9).…”
Section: Introductionmentioning
confidence: 75%